2008
DOI: 10.1021/ja800575v
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface Basal Planes of Layered Mixed Metal Oxides in Selective Transformation of Lower Alkanes: Propane Ammoxidation over Surface ab Planes of Mo−V−Te−Nb−O M1 Phase

Abstract: The surface ab planes of the M1 phase exposed selectively after atomic layer deposition (ALD) of alumina followed by crushing showed significantly improved selectivity to acrylonitrile during propane ammoxidation. The results demonstrated the importance of surface ab planes for the activity and selectivity of the M1 phase in propane ammoxidation and general utility of surface modification by ALD in studies of catalytic behavior of surface planes in layered mixed metal oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
0
47
0
3
Order By: Relevance
“…Catalytic experiments trying to verify the assignment of the minority {001} faces as location of active sites gave conflicting results. [20][21][22] Approximately 80% of the catalyst surface area accounts for the lateral surface of the cylindrical M1 particles. Electron microscopy has shown that the latter is characterized by a stepped morphology presumably resulting in similar terminating metal-oxo arrangements like on the basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic experiments trying to verify the assignment of the minority {001} faces as location of active sites gave conflicting results. [20][21][22] Approximately 80% of the catalyst surface area accounts for the lateral surface of the cylindrical M1 particles. Electron microscopy has shown that the latter is characterized by a stepped morphology presumably resulting in similar terminating metal-oxo arrangements like on the basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear as yet [42][43][44] that the active sites of the M1 phase are exclusively located on the (001) basal faces (''a-b plane'') of the needle morphology [42] but there is strong and general belief that the (001) face contains the motif of the active site that may exist in the termination structure of the whole surface of the material. For this reason the exact crystallographic analysis [40,45] of the basal plane structure not only in terms of its connectivity but also in terms of its cation ordering statistics [45][46][47] is of particular relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor impacting catalysis is the location of these sites. In one study, atomic layer deposition with alumina was employed to passivate the ab planes [60]. These passivated catalysts show very low conversion (<15%) with almost >95% selectivity to CO x , compared to catalysts where the ab planes are exposed where propane conversion of 40%-65% and acrylonitrile selectivity of 50%-70% were achieved [60].…”
Section: Propane Ammoxidation To Acrylonitrilementioning
confidence: 99%